2009
DOI: 10.1103/physrevlett.102.086102
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Dissipation in Epitaxial Graphene Films

Abstract: We have studied friction and dissipation in single and bilayer graphene films grown epitaxially on SiC. The friction on SiC is greatly reduced by a single layer of graphene and reduced by another factor of 2 on bilayer graphene. The friction contrast between single and bilayer graphene arises from a dramatic difference in electron-phonon coupling, which we discovered by means of angle-resolved photoemission spectroscopy. Bilayer graphene as a lubricant outperforms even graphite due to reduced adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
388
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(448 citation statements)
references
References 23 publications
39
388
2
8
Order By: Relevance
“…By comparing it with the first result, this friction force distribution matches well with the simulation result and the friction force along armchair orientation is also larger than the zigzag orientation. Due to the difference of the thickness between the two graphene sheets, the friction force of the thinner graphene (first result) is larger than the thicker one (second result), which is consistent with the published papers [36,37]. Both of the two experimental results show that the friction forces vary with the lattice orientations of graphene.…”
Section: Resultssupporting
confidence: 80%
“…By comparing it with the first result, this friction force distribution matches well with the simulation result and the friction force along armchair orientation is also larger than the zigzag orientation. Due to the difference of the thickness between the two graphene sheets, the friction force of the thinner graphene (first result) is larger than the thicker one (second result), which is consistent with the published papers [36,37]. Both of the two experimental results show that the friction forces vary with the lattice orientations of graphene.…”
Section: Resultssupporting
confidence: 80%
“…Finally, Fig. 1-(d) shows the LFM scan of the same area where two regions with different friction are identified: the low-friction region A corresponds to the Gr coating, the high-friction region B to bare Au, as explained in earlier friction experiments on Gr [6]. Identically prepared Gr-coated quartz crystals were inserted into a QCM mounted and annealed to about 200 • C overnight in an UHV chamber housing the cold head of a 4 K cryocooler [17].…”
mentioning
confidence: 73%
“…Its nanofriction behavior has been investigated mainly by frictional force microscopy [3][4][5]. Measurements on few-layer graphene and single-layer graphene, prepared by micromechanical cleaving on weakly adherent substrates, have revealed that friction monotonically increases as the number of layers decreases [2,6,7], while, surprisingly, recent studies showed that this tendency is inverted when graphene is suspended [8].Here we present the results of a quartz crystal microbalance (QCM) study mainly focused on the sliding of Xe monolayers on graphene (Gr) between 20 and 50 K, a temperature range which has been scarcely investigated in the literature [9], despite its relevance for the formation of condensed two-dimensional phases of many simple gases [10]. In our approach, the gold electrodes of a QCM were covered with Gr because the ample availability of phase diagrams of noble gases monolayers adsorbed on graphite [10] facilitates the interpretation of the QCM sliding measurements [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…with nano-scale contacts, in a number of different graphene systems. These systems include graphene epitaxially grown on SiC [97], exfoliated graphene transferred on SiO 2 [98,99], suspended graphene membranes [99,100], and graphene grown by chemical vapor deposition (CVD) on metals [101][102][103]. Because of this frictional reduction, many studies indicate graphene as the thinnest solid-state lubricant and anti-wear coating [104][105][106].…”
Section: Layered Materialsmentioning
confidence: 99%